Social-class differences in self-concept clarity and their implications for well-being. (June 2018) - Na, Jinkyung; Chan, Micaela Y; Lodi-Smith, Jennifer; Park, Denise C
A consistent/stable sense of the self is more valued in middle-class contexts than working-class contexts; hence, we predicted that middle-class individuals would have higher self-concept clarity than working-class individuals. It is further expected that self-concept clarity would be more important to one's well-being among middle-class individuals than among working-class individuals. Supporting these predictions, self-concept clarity was positively associated with higher social class. Moreover, although self-concept clarity was associated with higher life satisfaction and better mental health, the association significantly attenuated among working-class individuals. In addition, self-concept clarity was not associated with physical health and its association with physical health did not interact with social class.